The Fibroblast Growth Factor Receptor 2 p.Ala172Phe Mutation in Pfeiffer Syndrome—History Repeating Itself. Issue 5 (26th March 2013) - Jay, Sally; Wiberg, Akira; Swan, Marc; Lester, Tracy; Williams, Louise J.; Taylor, Indira B.; Johnson, David; Wilkie, Andrew O.M.
Abstract Pfeiffer syndrome is an autosomal dominant condition classically combining craniosynostosis with digital anomalies of the hands and feet. The majority of cases are caused by heterozygous mutations in the third immunoglobulin‐like domain (IgIII) of FGFR2, whilst a small number of cases can be attributed to mutations outside this region of the protein. A mild form of Pfeiffer syndrome can rarely be caused by a specific mutation in FGFR1. We report on the clinical and genetic findings in a three generation British family with Pfeiffer syndrome caused by a heterozygous missense mutation, p.Ala172Phe, located in the IgII domain of FGFR2. This is the first reported case of this particular mutation since Pfeiffer's index case, originally described in a German family in 1964, on which basis the syndrome was eponymously named. Genetic analysis demonstrated the two families to be unrelated. Similarities in phenotypes between the two families are discussed. Independent genetic origins, but phenotypic similarities in the two families add to the evidence supporting the theory of selfish spermatogonial selective advantage for this rare gain‐of‐function FGFR2 mutation. © 2013 Wiley Periodicals, Inc.